Influence of interleukin 1 beta on tenascin distribution in human normal and osteoarthritic cartilage: a quantitative immunohistochemical study. Issue 10 (October 1996) - Chevalier, X; Claudepierre, P; Groult, N; Godeau, G J
Abstract : OBJECTIVE: To determine the influence of IL-1 beta on the presence and the distribution of tenascin in matrix of human normal and osteoarthritic cartilage explants. METHODS: Cartilage was grown in organotypic culture with or without IL-1 beta (10 ng ml1). Tenascin antigen was detected on cryopreserved cartilage sections by immunohistochemical techniques with a monoclonal antibody directed against all tenascin isoforms (BC-4), and then quantified by video imaging densitometry. RESULTS: Tenascin was present in normal cartilage explants and increased in osteoarthritic cartilage explants. Treatment of normal and osteoarthritic cartilage explants with IL-1 beta (10 ng ml-1) induced an increase in tenascin content, which was particularly high in normal cartilage and predominated in the superficial layers of damaged cartilage. There was no obvious correlation between proteoglycan loss and presence of tenascin. CONCLUSIONS: In human normal and osteoarthritic cartilage explants, the presence and the distribution of tenascin are influenced by IL-1 beta.